Anti-Poverty Work: Unions, Poor Workers and Collective Action in Canada - Coulter, Kendra (Rethinking the Politics of Labour in Canada, 2012)
[T]his chapter identifies different forms of anti-poverty work being pursued in Canada today and examines the relations among poor people, poverty and labour unions. ...[The author] concentrates on examples of three main intersections of labour union and anti-poverty relations: union organizing of low-wage workers, poor workers' organizations, and multi-organization campaigns and coalitions. --Editors' introduction
Keywords: History; Labor Unions; Labor movement; Political activity; Political aspects